2017
DOI: 10.4103/ijccm.ijccm_79_17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Patients with Posterior Reversible Encephalopathy Syndrome

Abstract: Aims:The aim of this study was to study the clinical features and outcomes of patients with posterior reversible encephalopathy syndrome (PRES) admitted to the Intensive Care Unit (ICU).Subjects and Methods:All adult patients admitted to our ICU with acute onset neurologic symptoms with focal vasogenic edema on magnetic resonance imaging (MRI) were included in the study. Data were collected on demography, coexisting illness, admission severity of illness, neurological symptoms, blood pressure, treatment initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In addition, renal dysfunction, hypoalbuminemia, and thrombocytopenia are independent risk factors of PRES, and potentially linked to the disease [2]. Kalaiselvan et al argue that the progression of PRES is caused by endothelial damage, exacerbated by vasoconstriction, and autoimmune activation [13]. All these conditions may be coinciding, creating a summative or multiplicative effect on the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, renal dysfunction, hypoalbuminemia, and thrombocytopenia are independent risk factors of PRES, and potentially linked to the disease [2]. Kalaiselvan et al argue that the progression of PRES is caused by endothelial damage, exacerbated by vasoconstriction, and autoimmune activation [13]. All these conditions may be coinciding, creating a summative or multiplicative effect on the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid-attenuated inversion recovery (FLAIR) is the imaging modality of choice to diagnose PRES and may display findings of white matter edema in the watershed areas of the posterior cerebrum. PRES has been shown to affect the posterior regions of the parietal and occipital lobes most commonly but has also been shown to affect the frontal and temporal regions with relative frequency [1,2,[4][5][6][7][8][9][10]13].…”
Section: Discussionmentioning
confidence: 99%
“…High blood pressure was observed in over 85% of these patients. It was concluded that prompt recognition and blood pressure control were essential to patients’ survival and recovering rate as well as limitation of residual deficits . The study of 120 cases with PRES reports that 42% of patients were treated with immunosuppressive medications (cyclophosphamide, tacrolimus, cyclosporine, mycophenolate, bevacizumab, rituximab, vincristine, methotrexate, hydroxychloroquine, 5‐fluorouracil, sirolimus, thalidomide, gemcitabine, paclitaxel, carboplatin, sorafenib, infliximab, and hydroxyurea) and 45% had autoimmune disorders such as thrombotic thrombocytopenic purpura, systemic lupus erythematosus, hypothyroidism, scleroderma, Crohn’s disease, ulcerative colitis, primary sclerosing cholangitis, rheumatoid arthritis, and insulin‐dependent diabetes mellitus …”
Section: Discussionmentioning
confidence: 99%
“…This is why aggressive management of hypertension as a factor that further exacerbates endothelial permeability is essential to prevent subsequent damage and to facilitate prompt recovery . Authors Fugate and colleagues concluded that PRES is highly associated with autoimmune disorders and suggests that endothelial damage is the basis of the pathophysiologic progression of the disease …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation